Simplified Dosing of Gentamicin for Treatment of Sepsis in Bangladeshi Neonates - Hossain, M. Monir (International Centre for Diarrhoeal Disease Research, Bangladesh, 2009)
Extended-interval dosing of gentamicin has several advantages over conventional multiple-daily dosing for the treatment of sepsis. The study was conducted to evaluate the pharmacokinetics of gentamicin for the treatment of neonatal sepsis in predetermined doses at 24- or 48-hour intervals, according to weight category, and to develop a simplified protocol for use in peripheral healthcare settings in developing countries. This prospective observational study was conducted among 59 neonates admitted to the Special Care Nursery at Dhaka Shishu Hospital, Bangladesh, with suspected sepsis and treated with antibiotics, including gentamicin. Intravenous dosing of gentamicin according to weight category was: 10 mg every 48 hours if the infant weighed <2,000 g (n=23), 10 mg every 24 hours if the infant weighed 2,000–2,249 g (n=12), or 13.5 mg every 24 hours if the infant weighed 2,500–3,000 g (n=24). Peak and trough concentrations of gentamicin and the presence of signs of nephrotoxicity and ototoxicity were determined. The mean±standard deviation peak concentration of gentamicin was 12.3±3.7 µg/mL in infants weighing <2,000 g, 9.6±3.1 µg/mL in infants 2,000–2,249 g, and 10.0±3.4 µg/mL in infants 2,500–3,000 g. Initial peak concentration of gentamicin was >12 µg/mL in 28.8% and initial trough concentration was >2 µg/mL in 6.8% of the subjects. No signs of nephrotoxicity or ototoxicity were detected. Favourable pharmacokinetic parameters found with the simplified dosing regimen suggest that it is safe for the treatment of neonatal sepsis.